Removal of Ni and Cu Ions from Aqueous Solution on to Lignite-Based Carbons - S.E. Samra (Adsorption Science & Technology, 2000)
Non-activated lignites were prepared by the carbonization of Egyptian lignite in a limited quantity of air at 500°C, 700°C and 900°C, respectively. Zinc chloride-activated carbons were also prepared by the carbonization of lignite with 20 wt%, 40 wt% and 60 wt% zinc chloride in a limited quantity of air at 600°C. The surface areas of the resulting samples were determined from nitrogen adsorption studies at 77 K and from carbon dioxide adsorption studies at 298 K. The functional acidic groups on the surface were determined by neutralization with aqueous solutions of NaHCO 3 , Na 2 CO 3 and NaOH, respectively. The sorption of Ni 2+ and Cu 2+ ions on the prepared carbons as well as on the as-received lignite (L) were investigated. The influence of the time of contact, the initial ion concentration and the temperature was studied and the kinetics of the process were investigated. Equilibrium sorption isotherms were determined and the results interpreted by applying the Freundlich and Langmuir equations. The surface area was found to generally increase with increasing carbonization temperature. For activated carbons, the surface area increased with an increase in the amount of zinc chloride used in the activation process. The chemisorption of Ni 2+ and Cu 2+ ions on lignite-based carbon was found to be a pseudo-second order process. The acid sites on the surface provide active sites for the chemisorption of Ni 2+ and Cu 2+ ions and a qualitative relationship was found to exist between the maximum sorption capacity of these metal ions and the total surface acidity.